Power Transformer Fire and Explosion: Causes and Control - Hoole, P.R.P.; Shirley, Rufus; Nurul Izzati, Hashim; Mohd Hafiez Izzwan, Saad; Azfar Satari, Abdullah; Al-Khalid, Hj Othman; K., Piralaharan; Aravind, CV; Hoole, S.R.H. (International Science Press, 2017)
An increasing number of failures of power transformers over the world has led to greater interest in building up much needed expertise in electric power transformers, from its design to both preventive and prescribed maintenance. Winding failure is a frequent cause of transformer failure, bushing failure leads of fire and explosion, but it is still uncertain whether the increasing failure of transformers may be related to increasing lightning activity or increasing electric energy of the transient, surge voltages generated by lightning, especially long continuing currents and rate of rise of currents. But there are other important causes as well which need close attention, including wearing out of the contact points of tap changers in power generating and substation transformers, and poor maintenance of transformer oil. This paper seeks to review some of the well-known causes that lead to transformer fire and explosion, and highlights the important parts of the power transformer that need careful selection, installation, maintenance and condition monitoring. Moreover the containment of fires and measures that help to prevent transformer explosions in case of transformer fires are also discussed. Keywords: Embedded systems, Smart Antenna; Adaptive Array; Artificial Neural Network.